2014
DOI: 10.1016/j.spinee.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cervical spine kinematics during in vivo dynamic flexion-extension

Abstract: BACKGROUND CONTEXT A precise and comprehensive definition of “normal” in vivo cervical kinematics does not exist due to high inter-subject variability and the absence of mid-range kinematic data. In vitro test protocols and finite element models that are validated using only end range of motion data may not accurately reproduce continuous in vivo motion. PURPOSE The primary objective of this study was to precisely quantify cervical spine intervertebral kinematics during continuous, functional flexion-extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…A shift beyond this limit would cause cervical spine instability and potentially lead to iatrogenic cervical SCI. [ 21 ] GS laryngoscopy was associated with a significantly greater change in the whole-length cervical spine curvature compared with the CTrach LMA and SOS laryngoscopy. Moreover, changes in the C0–1 and C1–2 Cobb angles for the GS group, as well as the C1–2 Cobb angle for the LMA and SOS groups, were above the physiological upper limit and potentially subject to secondary SCI.…”
Section: Discussionmentioning
confidence: 99%
“…A shift beyond this limit would cause cervical spine instability and potentially lead to iatrogenic cervical SCI. [ 21 ] GS laryngoscopy was associated with a significantly greater change in the whole-length cervical spine curvature compared with the CTrach LMA and SOS laryngoscopy. Moreover, changes in the C0–1 and C1–2 Cobb angles for the GS group, as well as the C1–2 Cobb angle for the LMA and SOS groups, were above the physiological upper limit and potentially subject to secondary SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Various in vitro and in vivo studies [31][32][33][34][35][42][43][44] have investigated the cervical spine kinematics under various external loading conditions, but few data have been reported on the physiological cervical disc deformation during dynamic neck motion. Most of the studies on disc biomechanics used finite element modeling methods and few reported the data of disc deformation [21,45].…”
Section: Discussionmentioning
confidence: 99%
“…Three-dimensional (3D) finite element modeling methods have been used to study cervical disc deformation under various simulated loading conditions [21][22][23][24][25][26]. Cervical interverterbral kinemeatics has also been investigated by using in vitro human cadaveric models [27][28][29][30] and in vivo human subjects [15,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…There are also built-in differences in the biomechanics between each level of the cervical spine, including the segmental contribution to the global ROM and instant center of rotation. [1][2][3]19,24,27,38 Miller et al reported that the correlation between neutral cervical posture and flexion or extension ROM was only strong at the C-4 and C-5 levels. 19 Wu et al demonstrated that neck flexion relied more on the middle cervical segments and less on the lower ones, and vice versa during extension.…”
Section: Discussionmentioning
confidence: 99%